Studies on the synthesis of tetrahydropyrans via oxa-Michael addition leading towards the total synthesis of Montanacin D - Ho, Annabel Xuan Ying (Nanyang Technological University, 2021)
The first chapter describes a facile stereochemical study and synthetic route towards di-substituted tetrahydropyran rings. The key steps performed in this section involve cross-metathesis and Ozone-Wittig reactions of each alkene substrate, followed by an efficient oxa-Michael cyclisation to give the di-substituted tetrahydropyran products in good yields. These tetrahydropyrans adopt chair-like conformations where diequatorial products are exclusively obtained under kinetic control. The second and third chapters explore an efficient total synthetic route towards Montanacin D. Considered as a unique member of its family, Montanacin D is of great interest as the tetrahydropyran is adjacent to the butenolide moiety, which provides conformational rigidity. The approach to the molecule is done by way of a convergent synthesis, where the key reactions involve high diastereoselectivity in the oxa-Michael step in mild conditions and a more efficient manner of forming the alkene bonds – methods established in the previous chapter.